Using a staircase procedure for the objective measurement of auditory stream integration and segregation thresholds - Spielmann, Mona I.; Schröger, Erich; Kotz, Sonja A.; Pechmann, Thomas; Bendixen, Alexandra (Frontiers in Psychology, 2013)
Auditory scene analysis describes the ability to segregate relevant sounds out from the environment and to integrate them into a single sound stream using the characteristics of the sounds to determine whether or not they are related. This study aims to contrast task performances in objective threshold measurements of segregation and integration using identical stimuli, manipulating two variables known to influence streaming, inter-stimulus-interval (ISI) and frequency difference (Δf). For each measurement, one parameter (either ISI or Δf) was held constant while the other was altered in a staircase procedure. By using this paradigm, it is possible to test within-subject across multiple conditions, covering a wide Δf and ISI range in one testing session. The objective tasks were based on across-stream temporal judgments (facilitated by integration) and within-stream deviance detection (facilitated by segregation). Results show the objective integration task is well suited for combination with the staircase procedure, as it yields consistent threshold measurements for separate variations of ISI and Δf, as well as being significantly related to the subjective thresholds. The objective segregation task appears less suited to the staircase procedure. With the integration-based staircase paradigm, a comprehensive assessment of streaming thresholds can be obtained in a relatively short space of time. This permits efficient threshold measurements particularly in groups for which there is little prior knowledge on the relevant parameter space for streaming perception.